Microstructure and mechanical properties of extruded Mg-Sn alloys with a heterogeneous grain structure - Lin Tong; Jing Jiang; Guangli Bi; Yuandong Li; Tijun Chen; Xiaoru Zhang; Daqing Fang (Journal of Magnesium and Alloys)
The high-strength Mg-7Sn alloys (wt.%) with a heterogeneous grain structure were prepared by low-temperature extrusion (230 °C) with the extrusion ratio of 9:1 (9E230) and 17:1 (17E230). The two extruded alloys contained fine dynamic recrystallization (DRX) grains (FG) and coarse unDRX grains (CG). The difference in deformability between CG and FG leads to the formation of heterogeneous grain structure. The average grain size and basal texture intensities increased while the volume fraction of CG decreased with increasing extrusion ratio. Tensile testing results indicated that the extruded 17E230 alloy exhibited higher tensile strengths than 9E230 alloy, whose tensile yield strength (σ0.2), ultimate tensile strengths (σb), and elongation to failure (εf) were 231.1 MPa, 319.5MPa, and 12.54% respectively. The high tensile strengths of the extruded alloy mainly originated from grain refinement, texture strengthening, precipitation strengthening from a great number of nano-scale Mg2Sn phases, solid solution strengthening and hetero-deformation induced (HDI) strengthening, while the good ductility of the alloy was also mainly attributed to grain refinement, activation of the non-basal slip systems and HDI hardening.